ROOTSTOCK AGE AND GROWTH HABIT INFLUENCE TOP GRAFTING IN Araucaria angustifolia - Rozimeiry Gomes Bezerra Gaspar (CERNE, 2017)
The objective of this study was to evaluate the technical viability and influence of the rootstock age and grafts growth habit on Araucaria angustifolia top grafting. Two rootstocks (8 and 35-year-old) were grafted with grafts originating from two growth habits (orthotropic and plagiotropic). We used the patch grafting technique in the middle and upper third of the crown of 8-year-old trees, and in the middle and lower third of 35-year-old trees, always near the apex in primary branches. The experiments were performed during the fall and spring/2015. The treatments consisted of: 8-year-old rootstocks and orthotropic grafts; 8-year-old rootstocks and plagiotropic grafts; 35-year- old rootstocks and plagiotropic grafts; 35-year-old rootstocks and orthotropic grafts. We evaluated graft survival throughout the experiment and at 16 months, we evaluated their survival, emission, and number and average length of sprouts. Top grafting is technically feasible for araucaria, with better results using younger rootstocks (8-year-old), especially with plagiotropic propagules and grafting in fall/2015 (71.9%). Growth habits of the grafts are maintained identically as original, independently of rootstock growth habit.